PELAKSANAAN PEMBELAJARAN PADA MASA PANDEMI COVID 19 DI SMP NEGERI 12 KOTA TANGERANG SELATAN - Yenny Merinatul Hasanah; Nurilah Hanum (Universitas Pendidikan Indonesia, 2022)
This study aims to determine the implementation of learning and the inhibiting and supporting factors during the Covid-19 pandemic at SMPN 12, South Tangerang City. This research is research with a qualitative approach through observation, document analysis, and interviews as data collection, with the subjects in this study consisting of school principals, heads of curriculum, educators, and students of SMPN 12 Kota Tangerang Selatan. The results of research on the implementation of learning and the inhibiting and supporting factors during the Covid-19 pandemic at SMPN 12 Kota Tangerang Selatan are the first implementation of learning according to procedures, providing material with videos or text in textbooks and assignments via Google classroom media. The supporting factors for online PBM are: (1) adequate quota; (2) modules during a pandemic; and (3) teachers who are qualified in their fields and master IT. The inhibiting factors for the online teaching and learning process are: (1) unavailable quotas; (2) Poor network signal in certain areas; (3) Students who wake up late; (4) Late collection of assignments.